TECHNOLOGY INTEGRATION AND DIFFERENCES IN PAI TEACHING APPROACHES: A COMPARATIVE STUDY BETWEEN URBAN & RURAL SCHOOLS - Faridatul Maulidah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the integration of information technology in Islamic Religious Education (PAI) learning and compare the differences in teaching approaches between schools in urban and rural areas. The background of this research is based on the rapid digitalization of education, which has not been fully accompanied by equal access to technology and improvements in the digital competencies of educators. This study uses a qualitative-descriptive approach with a comparative study method through observation, interviews, and documentation in two schools with different environmental characteristics. The results show that schools in urban areas have a more optimal level of technology utilization, such as the use of online learning platforms, interactive media, and digital applications to support the PAI learning process. In contrast, schools in rural areas still rely on conventional methods such as lectures and face-to-face discussions due to limited technological facilities and network infrastructure. Nevertheless, the learning approach in rural areas is considered more contextual and effective in shaping the religious character of students. This study concludes that optimizing technology integration in PAI learning must be adapted to local social, cultural, and infrastructure conditions, accompanied by improving teacher competency and developing Islamic learning models that are in harmony with advances in digital technology.